PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 009 BINIO JAYA - Iin Firnawati; hendri Marhadi; Otang Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: the background of the problems in this study was lower student learning outcomes. With an average value of 64.59%, this research aims to improve learning outcomes IPS Elementary School fourth grade students 009 Binio Jaya. By implementing cooperative learning model Numbered Head Together, basic research used is classroom action research (PTK) is conducted in two cycles each cycle consisting of 2 meetings delivered material and one daily test .the research meetings held in March and April with the number of 32 students consisting of 16 male and 16 female, in order to study the class action is successful then compile research stages of planning action, observation and reflection, while the data collection instruments of observation and achievement test data analysis techniques used in the following activities teachers, activity 1,54,1% meeting with enough categories, meeting 2,66,6% with the good category, meeting IV 91.6% with very good category, student activities at the meeting of 1.54,1% with enough categories, meeting 2 , 62.5% with the good category, meeting IV 70.8% with the good category, a meeting V 75% in both categories, an increase in the basic learning outcomes of students' scores namely 58.96 increased to 62.93 (6%), the replay Daily I rise on a daily test II to 73.28 (24%), from this study be concluded that by applying the Cooperative Learning Model Numbered Heads Together (NHT) can improve learning outcomes of fourth grade students of SDN 009 Binio Jaya.Keywords : Implementation of Cooperative Learning Model Numbered Head Together (NHT) in improving learning outcomes.